Pengaruh Ekstrak Daun Sirih dan Metode Ekstraksinya Dalam Menghambat Penyakit Antraknosa pada Cabai Pascapanen - Desi Trisnawati; Lilik Pujantoro Eko Nugroho; Efi Toding Tondok (Jurnal Fitopatologi Indonesia, 2019)
Extract of Piper betle as An Inhibitor of Anthracnose Postharvest Disease on Chili Pepper Chili is a horticultural commodity that mostly needed by consumers in the fresh condition. However, there is an interval of time needed to deliver it from producers (farmers) to consumers. During the supply chain, deterioration of the quality of chilli fruit can occur by the presence of anthracnose disease caused by Colletotrichum spp. The use of syntetic fungicides to control anthracnose disease is not recommended because it will leave residues that are harmful to consumers. The alternative that can be done is to use botanical pesticides as fungicides. The aim of this research is to study the potential of Piper betle leaves extract (PLE) in inhibiting the development of the antracnose disease caused by Colletotrichum acutatum on the chili during storage. The sequences of this research were strarted with production of PLE by boiling method which was preceded by blanching, chopping, and without treatment of betel leaves, then bioassay of betel extract by measuring the diameter of fungus growth on PDA+ PLE. The third test was application of PLE on fresh chili fruits by spraying and soaking, continued by observed the antracnoseinsidence on chili during storage time (21 days). The results showed that the chopping method was the best betel leaf extraction method among other treatments, the use of 10% PLE concentration was the most effective concentration in inhibiting the growth of C. acutatum in vitro, spraying treatment using 10% EDS was the most effective in inhibited the insidence of anthracnose disease.